Analisis Implementasi Program Corporate Social Responsibility (CSR) PT. Perawang Sukses Perkasa Industri (PT. PSPI) di Kecamatan Kampar Kabupaten Kampar Provinsi Riau Dalam Perspektif Lingkungan - Belilasari Belilasari; Thamrin Thamrin; Sofyan Husein Siregar (Dinamika Lingkungan Indonesia, 2017)
This study was conducted from June to September 2016 and located in Kampar Sub-district, Kampar District, Riau Province. This study aims to analyze the implementation of corporate social responsibility program at PT. PSPI in public service environment and environment around the period 2013-2015, analyze the factors that influence the implementation of CSR program and analyze the most dominant factor in the implementation of CSR program in PT. PSPI period 2013-2015. The results of this study explain that PT. PSPI conducts its CSR program well, among others: sustainable development infrastructure, religious facilities, sports facilities, health facilities, community economy and education for the community around the company. So that public relations as well as the Company continues to run well and give confidence to the public that the company has a concern in the field of CSR. Based on the results of research on the implementation of public services that the Company is more focused on Economic and Social aspects when developing CSR programs because the community has an influence on the existence of the company. Each of the company's operational activities will have the potential to positively and negatively impact the communities surrounding the company. If companies pay attention to social aspects then the company will be able to achieve development and sustainable development. Companies in conducting business activities are not only oriented to profit only. Although achieving maximum profit is the main purpose of the establishment of a company, but the company can not achieve these benefits at the expense of the interests of other stakeholders ie stakeholders. Every company has responsibility for its actions and business activities that have an impact, either directly or indirectly on the stakeholders and the environment in which the company is located.